Building Religious Moderation Based on Al-Qur'an Values in Education in Medan Tembung District - Agusman Damanik; Cindy Irawati Ramadani; Nadja Arija Azukma; Ahmad Rizki Pratama; M Wardaya (QISTINA: Jurnal Multidisiplin Indonesia, 2022)
Religious moderation is the moderate understanding and practice of worship in religion, balanced, not extreme and exaggerated. Islam is a religion of rahmatan lil 'alamin, so religion needs to be manifested to become a problem solver in overcoming national problems. One of the nation's problems is the existence of radicalism thoughts and movements, namely thoughts and behaviors that put more emphasis on religious understanding which is harsh and extreme in nature and has an impact on the behavior of religious intolerance. Therefore, there is a need for religious moderation as a solution. Educational institutions are one of the strategic tools and are very appropriate to be "laboratories of religious moderation". Schools as educational institutions can build Qur'an-based religious moderation on the condition that exclusive views and acts of violent extremism in religious cloaks will damage the joints and fabric of a pluralistic nation. There are three main ways in which radical understanding and intolerance can penetrate the school environment; First, extracurricular activities. Second, the role of the teacher in the teaching and learning process. Third, through weak school policies in controlling the entry of radicalism in schools.